TEACHING ENGLISH IN THE AGE OF ARTIFICIAL INTELLIGENCE: SMART TOOLS, SMART LEARNERS - Bazarova Sevara Rustamovna (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract.  This  article  analyzes  the  impact  of  artificial  intelligence  (AI) technologies on the English language teaching process, based on the concepts of “smart tools”  and  “smart  learners”.  The  study  examines  the  effectiveness  of  AI-based language  learning  platforms,  automatic  translation  systems,  speech  recognition technologies, and adaptive learning systems. It also covers the role of the teacher in a modern educational environment, the development of digital literacy, and students’ independent learning abilities. The article analyzes the possibilities and limitations of artificial intelligence in modernizing the English language teaching process.